Analisis Faktor-faktor Penyebab Kendala Pengenaan Pajak pada Sektor Informal di Indonesia: Analysis of Factors Causing Impediments to Taxation in the Informal Sector in Indonesia - Ilham Febri Budiman (Universitas Bojonegoro, 2025)
Indonesia's informal sector plays an important role in the economy, particularly in terms of employment and contribution to Gross Domestic Product (GDP). However, the sector also faces significant challenges related to tax compliance, which hinders its contribution to state revenue. This study aims to analyse the factors that make it difficult to tax and its impact on fiscal revenue in Indonesia. The method used is a qualitative approach with literature studies and secondary data. The results show that low tax literacy, the complexity of the tax system, and the high threshold of taxable entrepreneurs (PKP) are the main factors affecting the low level of tax compliance of the informal sector. The vast and diverse informal sector also makes it difficult to record properly, resulting in relatively low state tax revenue from this sector.